Designing Six Models of Indonesian Waqf Bank Organizational Structures for Developing Islamic Finance - Pangestu, Raden Ali; Trihastuti, Aselina Endang; Sitasari, Ita; Hamidiyah, Emmy; Mohd Saufi, Mohd Shahid Azim; Mohammedi, Ssonko; Fauzi, Muhamad (Universitas Djuanda, 2025)
The discussion of waqf has become a trend among academics and practitioners of Islamic economics in Indonesia in the last decade with waqf regulations and great potential. Cash waqf as a productive waqf has great potential to develop long-term Islamic financial investment for the establishment of future waqf banks. A critical issue in the establishment of waqf banks is through academic discussions and debates on how to design the ideal waqf bank organizational structure in Indonesia. Previous research on waqf banks was dominated by regulations, cash waqf, asset waqf and waqf literacy. The research aims to offer a model of the organizational structure of waqf banks in Indonesia in the future. A qualitative method with a grounded theory approach is the ideal conception of a waqf bank. The data was sourced from interviews with micro waqf bank practitioners in Banten province and data analysis with design thinking because it excels in understanding user problems. The study found six models of the ideal organizational structure applied by waqf banks in Indonesia, namely the ad-hoc committee of establishment, form of ownership, shareholders, managers, implementers, deposit guarantee institutions, auditors, and human resource recruitment standards. The research implies that the ideal application of the organizational structure of waqf banks in Indonesia in developing long-term Islamic finance will achieve the principles of sharia, legitimacy and efficiency. Research is conceptually limited and needs to be developed and tested using quantification as a consideration for the establishment of waqf banks in Indonesia.